Arbitrarily Tunable Phase Shift in Low-Frequency Multiphase Oscillator - Roman Šotner; Ladislav Polák; Jan Jeřábek; Winai Jaikla (IEEE Transactions on Instrumentation and Measurement, 2023)
A special electronically tunable multiphase oscillator with arbitrarily and continuously adjustable phase shifts is introduced. Our design assumes to set the phase around the asymptotical limit of 180°. These features cannot be easily achieved by a standard way, i.e., any simple single-phase oscillator supplemented by a first-order adjustable all-pass section (shifter). The proposed design uses an electronically linearly tunable quadrature oscillator with frequency range from 0.98 up to 12.54 kHz. It also offers multiples of 45° as the initial setting of the phase shift tuning region. The example of operation shows the adjustment of the phase shift at a specific frequency (10 kHz) within the range of ±45° and around -180°, -135° and -90°. This variability is not available in standard cases without the use of several all-pass sections. The current value of the phase shift of the presented oscillator is electronically controlled and does not influence the oscillation frequency and condition of oscillation. Output levels of produced signals are not influenced by this tuning process and are in the range of several hundred mV. Two applications of the oscillator are proposed. The first one focuses on low-bitrate modulation systems (phase shift keying) while in the second one our circuit represents a source of phase-adjustable signals in acoustic experiments. Discrete passive elements and active devices (special multipliers having current output terminals, unity-gain differential voltage buffers) fabricated in 0.35 μm I3T25 ON Semiconductor 3.3 V CMOS process are used in experimental verification.
Keywords: Analog and Mixed-Signal Circuit Design; Advancements in PLL and VCO Technologies; Radio Frequency Integrated Circuit Design